Sosialisation Of The Ordinary Least Square (OLS) Method Inthe Analysis Of Economic Growth Factors During The New Normal Of Covid-19 In Padangsidimpuan City - Lilis Saryani; Hery Dia Anata Batubara; Ahmad Sayuti Pulungan (Yayasan Perguruan Kampus, 2024)
The Government of the Republic of Indonesia has now entered a newnormal phase of COVID-19 which has been running for almost two yearswhere the Covid-19 pandemic period is still ongoing even though it hasbegun to decline starting in 2021 yesterday. However, this new normal isstill unable to restore the existing situation as it was before the pandemic,one of which is the economic sector of the Indonesian people. The economicsector has had a very bad impact during the Covid-19 pandemic, becauseall previous economic activities of the community are still moving withconventional systems. This is deeply felt by business actors in traditionalmarkets. The problem that occurs is that business actors are unable to risequickly and are unable to compete with other business actors who arebetter prepared to make sales during the pandemic.The purpose of this study is to learn about the analysis of economic growthfactors during the new normal period of the Covid-19 pandemic inPadangsidimpuan City by applying the Ordinary Least Square (OLS)method by utilizing technology as a promotion / marketing of products soldby business actors in the Sangkumpal bonang market in Padangsidimpuancity. The analysis method used in this study is a quantitative method usingpanel data using A Fixed Effect Model, the steps of this study are thecollection of secondary data obtained from the Central Statistics Agency ofthe Agency after data analysis. Based on the results of the analysis obtainedfrom the results of the study: partially using the Fixed Effect Model Analysistool, it produces negative variables on the Human Development Index inPadangsidimpuan City, comparing the Economy related to the EconomicGrowth Index of the community in Padangsidimpuan City.